Douglas Field, Walking in the Dark: James Baldwin, My Father, and Me - Janina Levin (European Journal of Life Writing)
In 1997, Geoff Dyer presented himself as a literary critic with an extreme case of writer’s block, attempting to write a book about D. H. Lawrence that he would never actually finish (Dyer did not intend to write a serious study of D. H. Lawrence). This persona appeared in Out of Sheer Rage: Wrestling with D. H. Lawrence, a strange, hybrid, cheeky work — part memoir, part travelogue, part literary criticism — that parodied the dry, high-toned academic literary criticism long dominant in universities. Dyer was not alone in his preference for the more down-to-earth mixture of memoir and literary criticism. A decade before Out of Sheer Rage was published, scholars and teachers grappling with the lack of funding for humanities programs and declining humanities majors believed it was time to validate a kind of literary criticism that would take readers back to literature’s humanist roots. They wondered what happened to all the inspired readers, those who found in great books the power to give them a voice and to think through life’s intractable problems.